FUNDAMENTALS OF THE IMPLEMENTATION OF FOREIGN EXPERIENCE IN THE FIGHT AGAINST THE STATE OF CORRUPTION IN THE PRESCHOOL EDUCATION SYSTEM AND ITS PREVENTION - Mamajonova Xushruy Shavkatovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
The article provides an analysis of foreign experience in combating and preventing the state of corruption in the preschool education system and regulatory legal acts issued by our state. The evolutionary stage of the reforms carried out in the field of preschool education on the issue of justice and legality in the society being renewed in the new development strategy of Uzbekistan was analyzed.